Hysteroscopy use in modern diagnostics and therapy - Stetkiewicz, Tomasz; Stachowiak, Grzegorz; Surkont, Grzegorz; Pawłowicz, Paweł; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
Hysteroscopy is used extensively in the evaluation of common gynaecological problems that were previously evaluated with blind and inaccurate techniques [e.g. premenopausal menstrual disorders, infertility and postmenopausal bleeding]. It allows direct visualization of the uterine cavity and the opportunity for targeted biopsy, safe removal of endometrial polyps, and treatment of submucous fibroids, septa and adhesions. Hysteroscopy is safe, with a low incidence of serious complications; it has a small failure rate. There is a general consensus that hysteroscopy is the current gold standard for evaluating intrauterine pathology, including submucous myomas, polyps, hyperplasia and cancer.